In-cell dehydration of sodium manganese hexacyanoferrate cathode revealed by solid-state NMR - Zonglin Li; Xiaobing Lou; Shinuo Kang; Dingming Liu; Fushan Geng; Ming Shen; Bingwen Hu (Magnetic Resonance Letters)
The hard-to-remove lattice water has been regarded as a significant obstacle impeding the practical use of Prussian blue analogue cathodes for sodium-ion batteries. This work monitored the electrochemical evolution of a hydrated monoclinic sodium manganese hexacyanoferrate cathode by solid-state nuclear magnetic resonance (NMR). For the first time, we established a correlation between the chemical shifts of 23Na NMR signals and the presence or absence of lattice water within this cathode. Through this method, we verified the electrochemical dehydration process that coincides with the merging of two redox platforms and a phase transformation in the initial cycles. Furthermore, we discovered that the lattice water is completely removed after several-day cell rest following a single activation cycle.